Աշխարհիմաստութիւնն իբրեւ հայոց ինքնութեան ուսումնասիրման եւ կառուցարկման գործօն (Հայկ Ասատրեանի օրինակով) - Արմէն Սարգսեան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье анализируется национальная идентичность армян в контексте геософских идей доктора философии Айка Асатряна (20-й век). Асатрян четко не определяет или эксплицирует понятие, однако в своих трудах он разделяет геософские и географические подходы к изучению проблемы национальной идентичности армян.The article analyzes the national identity of the Armenians in the context of the geosophical ideas of Hayk Asatryan (doctor of philosophy, 20th century). Asatryan does not clearly defi ne or explicate the concept of geosophy, but in his works he demarcates geosophical and geographical approaches to the study of the problem of the national identity of the Armenians.
Keywords: Christianity; Armenian church